Evaluation of Nurse-Midwive’s Practices about Immediate Postpartum Care for Mothers - Sanaa Hussein Ali, Hawraa Hussein Ghafel (Pakistan Journal of Medical & Health Sciences, 2022)
The first two hours following delivery are known as the immediate postpartum phase. Quality nursing care and competent health care workers, particularly experienced birth attendants, are essential requirements for providing care for both mothers and infants during this early or acute phase of the postpartum period. To determine the quality of health care services based on patient health outcomes, the most critical intervention for minimizing maternal and neonatal morbidity and mortality is to provide quality health care directly after the critical period of labor and delivery. Objective: To evaluation of Nurse-midwives’ practices about Immediate Postpartum Care for mothers. Methodology: descriptive and analytic study conducted to evaluate nurses’ and midwives’ practices on immediate postpartum care for mothers. The study was started at 1st of September 2021, to 25th of March 2022. A non-probability (purposive sample) included (50) nurse-midwives who work in the Maternity Teaching Hospital’s delivery room. A pilot study is done to determine the questionnaire’s reliability. SPSS (24) version was used to examine the data. Results: According to the study findings, (94 %) of nurse-midwives demonstrated a fair level of practice when evaluating nurse-midwives’ practices for Immediate Postpartum Care. Conclusion and Recommendations: The study shows that nurse-midwives they had a fair level of Immediate Postpartum Care for mothers. However, nurse-midwives require further educational programs to improve their practices, experiences, and skills in order to provide high-quality postpartum care to mothers.